Assessing Institutional Readiness for Blended Learning Management and Implementation in Malaysian Higher Education - Kathirveloo, Punitha (Management Research Journal, 2024)
This paper aimed to examine the readiness of Malaysian Higher Education Institutions (HEIs) to improve teaching and learning activities in Higher Education Institutions (HEIs) by emphasizing on the practice of good governance by Ministry of Higher Education (MOHE) by emphasizing on the practice of good governance by Ministry of Higher Education (MOHE) through the deployment of National E- Learning Policy (DePAN 2.0). The policy incorporates six domains: infrastructure and infostructure, governance, e-content, blended learning, professional development and enculturation through a strategic e-learning framework to facilitates HEIs towards globalised online learning. The discussion is further broadened into exploring the four concepts of good governance: accountability, participation, persistency, transparency and its governing influence towards the application of six domains from DePAN 2.0 as the mechanism to constantly monitor and assess the effectiveness of blended learning management and implementation in HEIs. A comparative analysis approach is used to study existing literatures, models and conceptual frameworks involving blended learning and governance in Malaysian Higher Education context contributing to key findings suggesting student acceptance and lecturer adoption significantly impact institutional readiness in blended learning implementation and effective governance is critical for promoting greater student acceptance and faculty adoption of blended pedagogies. This study findings have profound impacts for policymakers and higher education institutions (HEIs), emphasizing the necessity for strategic interventions to enhance governance practices, support faculty development, and foster a conducive learning environment to fully leverage the benefits of blended learning in Malaysia’s higher education landscape.